2023
DOI: 10.3390/ma16103713
|View full text |Cite
|
Sign up to set email alerts
|

Static and Fatigue Mechanical Performance of Abutments Materials for Dental Restorations

Abstract: The choice of the proper restorative material is essential for the long-term success of implant-supported rehabilitations. This study aimed to analyze and compare the mechanical properties of four different types of commercial abutment materials for implant-supported restorations. These materials included: lithium disilicate (A), translucent zirconia (B), fiber-reinforced polymethyl methacrylate (PMMA) (C), and ceramic-reinforced polyether ether ketone (PEEK) (D). Tests were carried out under combined bending–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…The confidence interval used for testing the hypothesis was 95%. A similar approach in evaluating small samples has been used by many authors in recent publications when testing and analyzing mechanical performance (tensile tests, bending, impact, hardness, coefficient of friction) of materials for dental restoration [24], resin-modified glass ionomer [25], metal-ceramic compatibility in dental restorations [26], materials containing nanohybrid filler [27] and hypoallergenic denture base resins [28].…”
Section: Resultsmentioning
confidence: 99%
“…The confidence interval used for testing the hypothesis was 95%. A similar approach in evaluating small samples has been used by many authors in recent publications when testing and analyzing mechanical performance (tensile tests, bending, impact, hardness, coefficient of friction) of materials for dental restoration [24], resin-modified glass ionomer [25], metal-ceramic compatibility in dental restorations [26], materials containing nanohybrid filler [27] and hypoallergenic denture base resins [28].…”
Section: Resultsmentioning
confidence: 99%
“…In dental implantology, PEEK may be utilized to produce both dental implants and implant abutments [93][94][95]. Fiber-reinforced PEEK composites used for dental implants and abutments even show stress distribution to the bone tissues [96]. Implant abutments made of PEEK show less accumulation of bacterial plaque on the surface compared to Titanium ones [97,98].…”
Section: Peekmentioning
confidence: 99%
“…Sahebi et al 15 evaluated the fracture resistance of monolithic zirconia, porcelain-veneered zirconia, and a control group of porcelain-fused-to-metal under thermocycling and concluded that monolithic zirconia presented higher fracture resistance than the bilayered restorations for screw-cement retained implantsupported restorations. However, few studies [16][17][18][19] have evaluated fatigue and fracture resistance of translucent monolithic zirconia crowns and the use of CoCr base abutments under chewing simulating.…”
Section: Introductionmentioning
confidence: 99%